PENGARUH NET PROFIT MARGIN TERHADAP OPERATING CASH FLOW RATIO PADA PERUSAHAAN SEKTOR PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2024 - Matius Putra; Nanu Hasanuh; Achmad Nawawi (Journal of Economic, Bussines and Accounting (COSTING), 2026)
The development of the property sector in Indonesia has shown significant dynamics, particularly in the post-pandemic period until 2024. This sector plays a strategic role in driving the national economy through infrastructure development, employment absorption, and increased investment activity. However, not all companies in this sector are able to generate good cash flow despite high profits. Therefore, by analyzing the effect of Net Profit Margin (NPM) on the Operating Cash Flow Ratio (OCFR), we can determine whether there is a relationship between profitability and cash flow. Using a quantitative research method with simple linear regression analysis on 32 research samples, the results showed that Net Profit Margin (NPM) did not have a significant effect on the Operating Cash Flow Ratio (OCFR). Although the regression coefficient indicates a positive relationship, the effect is not statistically strong enough to explain the variation in OCFR changes, so the hypothesis is rejected and H0 is accepted. Therefore, there are other factors outside the research model. This finding indicates that profitability does not always align with a company's ability to generate operational cash flow, particularly in the property sector.